Somalia--the untold story : the war through the eyes of Somali women - Gardner, Judith; El-Bushra, Judy (CIIR ; Pluto Press, 2004)
Somalia came to the world's attention in 1992 when television and newspapers began to report on the terrifyingly violent war and the famine that resulted. Half a million Somalis died that year, and over a million fled the country. Cameras followed US troops as they landed on the beaches at Mogadishu to lead what became an ill-fated UN intervention to end hunger and restore peace. In this book, Somali women write and talk about the war, their experiences and the unacceptable choices they often faced. They explain clearly, in their own words, the changes, challenges - and sometimes the opportunities - that war brought, and how they coped with them. Key themes include the slaughter and loss of men, who were the prime target for killings; rape and sexual violence as a weapon of war; changing roles in the family and within the pastoralist economy; women mobilising for peace; and leading social recovery in a war-torn society. This book is not only an important record of women's experience of war, but also provides researchers and students of gender and conflict with rare first hand accounts highlighting the impact of war on gender relations, and women's struggle for equal political rights in a situation of state collapse.